2017
DOI: 10.1523/jneurosci.3316-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Signaling by FGF Receptor 2, Not FGF Receptor 1, Regulates Myelin Thickness through Activation of ERK1/2–MAPK, Which Promotes mTORC1 Activity in an Akt-Independent Manner

Abstract: FGF signaling has emerged as a significant "late-stage" regulator of myelin thickness in the CNS, independent of oligodendrocyte differentiation. Therefore, it is critically important to identify the specific FGF receptor type and its downstream signaling molecules in oligodendrocytes to obtain better insights into the regulatory mechanisms of myelin growth. Here, we show that FGF receptor type 2 (FGFR2) is highly enriched at the paranodal loops of myelin. Conditional ablation of this receptor-type, but not FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 71 publications
4
45
1
Order By: Relevance
“…We have recently shown that during active myelination, downregulation of myelin gene expression and myelin growth in conditional Erk1/2‐dKO mice is accompanied by a significant reduction in the expression of p‐mTOR, p‐Raptor, p‐p70S6K, and p‐S6RP, but not of p‐Akt. Since Akt is upstream of mTORC1 and p‐mTOR, p‐Raptor, p‐p70S6K, and p‐S6RP are traditionally considered downstream effectors in the PI3K/Akt/mTORC1 pathway, our earlier work suggested convergence of the two pathways at the level of mTORC1 (Figures and and Furusho et al, ). However, it was unclear whether the observed changes in the expression levels of these signaling molecules had any functional significance with respect to ERK1/2 signaling regulating myelin growth.…”
Section: Discussionmentioning
confidence: 87%
“…We have recently shown that during active myelination, downregulation of myelin gene expression and myelin growth in conditional Erk1/2‐dKO mice is accompanied by a significant reduction in the expression of p‐mTOR, p‐Raptor, p‐p70S6K, and p‐S6RP, but not of p‐Akt. Since Akt is upstream of mTORC1 and p‐mTOR, p‐Raptor, p‐p70S6K, and p‐S6RP are traditionally considered downstream effectors in the PI3K/Akt/mTORC1 pathway, our earlier work suggested convergence of the two pathways at the level of mTORC1 (Figures and and Furusho et al, ). However, it was unclear whether the observed changes in the expression levels of these signaling molecules had any functional significance with respect to ERK1/2 signaling regulating myelin growth.…”
Section: Discussionmentioning
confidence: 87%
“…For Figs 1, 3 and 5, mouse tissues were fixed by cardiac perfusion of fixative, which consisted of 2.5% glutaraldehyde and 1% paraformaldehyde in 150 mM sodium cacodylate, pH 7.4 (all from Electron Microscopy Sciences, Hatfield, PA). The tissues were harvested as described for parotid salivary gland (Terasaki et al, 2013) and spinal cord (Furusho et al, 2017). The fixed tissues were processed by the ROTO protocol (Tapia et al, 2012), in which the tissue is incubated successively in reduced osmium, thiocarbohydrazide and unreduced osmium.…”
Section: Methodsmentioning
confidence: 99%
“…Although deletion of each of these proteins, or their cognate receptors, impaired OL myelination to some extent (Cellerino, Carroll, Thoenen, & Barde, 1997; Furusho, Ishii, & Bansal, 2017; Joseph D'Ercole & Ye, 2008; Kahn et al, 1999; Vondran, Clinton‐Luke, Honeywell, & Dreyfus, 2010; Ye, Li, Richards, DiAugustine, & D'Ercole, 2002; Zeger et al, 2007), it is unclear whether they are both necessary and sufficient to drive OL myelination, analogous to NRG1 type III in the PNS. The precise physiological cellular sources of these growth factors and the signals controlling their production and release are currently being elucidated.…”
Section: Myelination and Mtormentioning
confidence: 99%